Developmental language disorders and risk of recidivism among young offenders. (14th July 2020) - Winstanley, Maxine; Webb, Roger T.; Conti‐Ramsden, Gina
Abstract : Background: Although factors such as adverse family background have been widely examined, little is known about the prevalence or potential impact of developmental language disorder (DLD) on risk of recidivism in young people with history of criminal justice system contact. Methods: A total of 145 young offenders participated. An adversity score was constructed based on information found in youth justice service records. Data collected included standardised measures of expressive and receptive language, nonverbal IQ and the inventory of callous–unemotional traits. Survival analysis was performed to examine differences in reoffending risk between young offenders with and without DLD. Results: The cumulative incidence of reoffending within a year of the young person's court order was markedly raised in the DLD group (62%; 95% CI 52, 72) versus the non‐DLD group (25%; 95% CI 16, 39). Furthermore, in the final multivariable survival analysis the independent elevation in risk linked with DLD was not greatly attenuated with adjustment for nonverbal IQ, adversity score, age at first offence, number of previous offences and deprivation score. DLD was the most significant predictor with an adjusted hazard ratio of 2.61 (95% CI 1.80, 3.78). Conclusions: Young offenders with DLD are more than twice as likely to reoffend than their unaffected offending peers. DLD is a powerful predictor of recidivism above and beyond other known risk factors.